Mais é melhor! mulheres no conselho de administração e a divulgação de responsabilidade social corporativa relacionada a gênero - Silva, Larissa Karoline Souza (2020)
The disclosure of information is a tool that aims to ensure transparency about the Corporate Social Responsibility (CSR) initiatives and the performance related to gender issues by the company. It is suggested that the participation of women enables a board of directors that is more sensitive to gender demands. Based on these issues, Critical Mass Theory and Tokenism Theory appear as a singular alternative for the theoretical support of the study. Critical Mass Theory affirms that at least three women on the board of directors are needed to influence the dynamic of the decision-making process. Tokenism Theory deals with four minority groups, with varying proportions of individuals, in which the increase in minority subjects in the groups makes it possible to form coalitions that affect the dynamics of the group. The aim of this study is to analyze whether the level of disclosure of information about CSR towards actions related to gender issues is influenced by the composition and number of women on the boards of directors of companies according to the Critical Mass Theory and the Theory of Tokenism. For this purpose, information was collected from 2.199 organizations from 52 countries that present information on CSR practices related to gender and composition of the board of directors in the Thomson Reuters Eikon database, referring to the period from 2010 to 2017. Descriptive statistics of data, mean difference test, simple correspondence analysis (Anacor) and panel data regression were performed. As a result, it is possible to highlight the average of 7,31 for the dissemination of gender information by organizations (of a maximum score of 10 points). Regarding the percentage of women on the boards, the average corresponded to 13,97% of women on the board of directors. In addition, it was found that about 22% of the study's observations had three or more women on the boards, in other words, they have critical mass. It was observed that, in relation to the dissemination of gender (DIVULG_GEN), companies with a critical mass of women had a higher average than companies without a critical mass, with the difference between these two groups being statistically significant at 1%. Regarding the companies that belong to countries that do or do not have specific regulations on quotas for women on the boards, there was also a significant difference in averages at 1%. In terms of correspondence analysis, there was a predominance of countries belonging to the inclined group, according to the division proposed by Tokenism Theory. Finally, it was found that the variables critical mass of women (THREE_WOMEN), size of the board (TAM_CADM), size of the company (TAM) and ROA were statistically significant. Thus, the research findings infer that the existence of a critical mass of women within the board of directors positively influences the level of disclosure of information about CSR related to the companies' gender.